2014
DOI: 10.1007/s00170-014-6432-0
|View full text |Cite
|
Sign up to set email alerts
|

Wear phenomena of grinding wheels with sol–gel alumina abrasive grains and glass–ceramic vitrified bond during internal cylindrical traverse grinding of 100Cr6 steel

Abstract: This article presents the results from a traverse internal cylindrical grinding process conducted using grinding wheels with sol-gel alumina abrasive grains and varying volumes of glass-ceramic vitrified bond. The aim was to determine how changing the bond volume within the range of V b =11.5-14.5 % influenced the wear phenomenon of the microcrystalline sintered corundum abrasive grains and the ceramic bond bridges with glass-crystalline structure. The paper presents grinding wheels with conic chamfer and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…The dominant microcrystalline active abrasive grain vertexes wear phenomenon is the creation of flat surfaces as a result of their plastic flow [28][29][30]. It has also been observed that the phenomena of oxide layer shedding and plastically deformed grain layers occur periodically on the smoothedout surfaces of the active vertexes [30,31]. This process is caused by fatigue and thermo-fatigue wear, as a result of which sharp edges of crystals located below the plastically deformed surface layer are uncovered ( Fig.…”
Section: Sol-gel Alumina Abrasives Wear Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant microcrystalline active abrasive grain vertexes wear phenomenon is the creation of flat surfaces as a result of their plastic flow [28][29][30]. It has also been observed that the phenomena of oxide layer shedding and plastically deformed grain layers occur periodically on the smoothedout surfaces of the active vertexes [30,31]. This process is caused by fatigue and thermo-fatigue wear, as a result of which sharp edges of crystals located below the plastically deformed surface layer are uncovered ( Fig.…”
Section: Sol-gel Alumina Abrasives Wear Phenomenamentioning
confidence: 99%
“…Sol-gel alumina abrasives dominant wear phenomenabased on drawings of the Rappold Winterthur Group and the authors' own material[31] …”
mentioning
confidence: 99%
“…With respect to experimental grinding tests, studies have been carried out to examine the influence of grinding parameters on wear evolution, and hence, on the efficiency of the process [8,10,11]. In this case, the main challenge of studying a specific type of wheel wear is in terms of isolating this from other types of wear.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, not only wear flat was found to occur, but also other kinds of simultaneous wear, with the evolution of wear flat being interrupted. Nadolny [11] conducted internal grinding experiments, showing not only wear flat on the abrasive wheel surface but also other kinds of wear. The aim of this study was to compare the wear behavior of different wheel configurations, varying the bond.…”
Section: Introductionmentioning
confidence: 99%
“…The tribochemical nature of wear flat raises the need to address this issue, mainly from the perspective of studying the grinding process or implementing tribological tests, particularly pin on disk tests. With respect to experimental grinding tests, studies have been carried out to examine the influence of grinding parameters on wear evolution, and hence, on the efficiency of the process [8], [10], [11]. In this case, the main challenge of studying a specific type of wheel wear is in terms of isolating this from other types of wear.…”
Section: Introductionmentioning
confidence: 99%